Intergenerational open learning: Case study of "Autobiografiamo" blog - Barbara Baschiera (Pensa MultiMedia, 2012)
This research aims to show what it is possible to accomplish through educational processes, which account for the language of technology's creative and communicative potential within the context of intergenerational learning. In fact, it is possible to promote relationship-making skills between subjects of different ages, to develop and to capitalise on the formative educational potential of the elderly, and to foster the build-up of inter-generational dialogue. To this end, an analysis with respect to the first intergenerational autobiographical online laboratory in Italy has been undertaken. The laboratory endeavoured to develop and capture, by narrative means, the wealth of historical knowledge and experience, as well as the cultural and social factors underlying our identity. At the same time, it enhances virtual mobility and creativity with a view to promoting knowledge accretion and dialoguing skills through the use of blogs.